Dynamic of Nanopowder Production During Laser Target Evaporation - Trigub M. V. Maksim Viktorovich; Platonov V. V. Vyacheslav Vladimirovich; Fedorov K. V. Kirill Valerjevich; Evtushenko G. S. Gennady Sergeevich; Osipov V. V. Vladimir Vasiljevich (2016, 2016)
Title screen